2018
DOI: 10.1021/acsbiomaterials.8b00986
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsically Fluorescent Silks from Silkworms Fed with Rare-Earth Upconverting Phosphors

Abstract: Fluorescent silk fibroin (SF) fibers have great potential in biomedical application and special functions for marking and tracking. How to fabricate fluorescent SF fibers with good fluorescence stability by a simple and environmentally friendly method has yet to be explored. Here, we successfully produced fluorescent SF fibers by using silkworms as bioreactors to introduce rare-earth upconverting phosphors (UCPs) into silk fibroin. The modified silk exhibited bright green colors under 980 nm laser. This direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 42 publications
(57 reference statements)
0
13
0
Order By: Relevance
“…[ 7,8 ] Therefore, feeding silkworms with nontoxic, biocompatible, environmental benign, highly luminescent, and low‐cost substances seems to be the optimal strategy to produce fluorescent silk. [ 9–11 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 7,8 ] Therefore, feeding silkworms with nontoxic, biocompatible, environmental benign, highly luminescent, and low‐cost substances seems to be the optimal strategy to produce fluorescent silk. [ 9–11 ]…”
Section: Introductionmentioning
confidence: 99%
“…
luminescent, and low-cost substances seems to be the optimal strategy to produce fluorescent silk. [9][10][11] Carbon dots (CDs) are the most competitive candidates for the above target, because they have shown outstanding biocompatibility and superior fluorescence in previous research such as bioimaging, [12,13] drug delivery, [14,15] and photothermal therapy. [16,17] In fact, many CDs are made from biomass, which guarantees the biosafety, low price, and green chemistry in CDs production.
…”
mentioning
confidence: 99%
“…It has been widely used in the biomedical field, textile industry, and even as an engineering material due to its favorable biocompatibility, controllable biodegradability, lustrous appearance, and excellent mechanical properties [ 1 , 2 , 3 , 4 ]. Various functional components, such as fluorescent proteins [ 5 ], rare-earth upconverting phosphors [ 6 ], antimicrobial agents [ 7 , 8 ], metal ions [ 9 ], metal and semiconductor nanodroplets [ 10 , 11 ], and graphene quantum dots [ 12 , 13 , 14 ], have been used to intrinsically produce functionalized silks. Extrinsic and intrinsic functionalization approaches have been used to improve the performance of silk.…”
Section: Introductionmentioning
confidence: 99%
“…The use of Ln-doped fibers in photonics is well-known, and several studies have reported that the presence of lanthanides can confer photochromic, luminescent and fluorescent properties as well as up-conversion ability to fibers. Examples could be Eu +3 or Dy +3 strontium aluminate luminescent fibers produced by a special spinning technology, with the substrate of polyester, nylon, or polypropylene resin ( Guo et al, 2011 ), fluorescent Pr +3 and Dy +3 -doped Chalcogenide fibers ( Chahal et al, 2016 ), Er +3 /Yb +3 /Tm +3 tri-doped tellurite glass microsphere coupled by tapered fibers ( Liu et al, 2020 ), fluorescent silks obtained from silkworms fed with rare-earth upconverting phosphors ( Zheng et al, 2018 ). Moreover, Ln-doped fibers have been employed in the production of lasers (amplifiers rare-earth-doped silica and fluorozirconate fibers, particularly erbium-doped fibers) ( Digonnet, 2001 ) and smart Dy +3 and Eu +3 doped stimuli-responsive textiles ( Shen et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%